2022
DOI: 10.3390/cells11020228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formyl Peptide Receptor Agonists Ac9-12 and WKYMV in In Vivo and In Vitro Acute Inflammatory Experimental Models

Abstract: Formyl peptide receptors (Fprs) are a G-protein-coupled receptor family mainly expressed on leukocytes. The activation of Fpr1 and Fpr2 triggers a cascade of signaling events, leading to leukocyte migration, cytokine release, and increased phagocytosis. In this study, we evaluate the effects of the Fpr1 and Fpr2 agonists Ac9-12 and WKYMV, respectively, in carrageenan-induced acute peritonitis and LPS-stimulated macrophages. Peritonitis was induced in male C57BL/6 mice through the intraperitoneal injection of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…Thus, species identification would be required prior to treatment, reducing its potential use in resource-limited settings. Further, the antagonist is not entirely specific to FPR2, exhibiting low affinity for other FPRs ( 59 ); thus, the potential influence of FPR1 and FPR3 cannot be entirely ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, species identification would be required prior to treatment, reducing its potential use in resource-limited settings. Further, the antagonist is not entirely specific to FPR2, exhibiting low affinity for other FPRs ( 59 ); thus, the potential influence of FPR1 and FPR3 cannot be entirely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments further corroborated that the agonist was capable of partially rescuing the expected infectivity, although not to levels observed in wildtype animals. Although we were particularly interested in the effects of FPR2 stimulation, WKYMVm acts as a non-specific agonist for FPRs 1, 2, and 3 ( 59 ). While our study primarily attributes the observed effects to the interaction between ANXA1 and FPR2, we cannot exclude the possibility that WKYMV may also be acting through these receptors.…”
Section: Discussionmentioning
confidence: 99%